The history of ethics in research with human subjects - DOI: 10.3395/reciis.v2.Sup1.203en - Miguel Kottow (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
This article contextualizes the emergence of the field of research ethics in historical, social, and political events over the last 60 years. It draws a distinction between professional ethics and bioethics, focusing on the historical and philosophical precedents of the latter field. It also presents the appearance of research ethics as a result of the disclosure of cases of scientific misconduct, discussing the first regulations on research ethics, the guidelines contained in the Belmont Report, and its influence on the creation of bioethical principlism. The article also analyzes the functioning of research ethics committees and possible limitations to scientific activity. Finally, it highlights some issues that remain unsolved, such as payment to research participants, the conduct of research on unconscious people, using children in experiments for testing new drugs or new therapeutic indications, the definition of minimum risk, and the way bioethics has been taking place in developing countries.